Herwarth Walden and DER STURM : Aritsts and Publications. (New York : Helen Serger, la boetie, inc., 1981)
Archipenko, Alexander ; Balla, Giacomo ; Bauer, Rudolph ; Berlewi, Henryk ; Boccioni, Umberto ; Bortnyik, Sandor ; Burliuk, Vladimir ; Campendonk, Heinrich ; Carra, Carlo ; Chagall, Marc ; Delaunay, Robert & Sonia ; Dexel, Walter ; Feininger, Lyonel ; Goncharova, Natalia ; Guttfreund, Otto ; etc.
Herwarth Walden and DER STURM, Helen Serger, la boetie, inc., New York, February 27 through May, 1981
boek